The Dialect of the West of England; Particularly Somersetshire - Jennings, James, 1772-1833 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Dialect of the West of England; Particularly Somersetshire" by James Jennings is a linguistic exploration written in the late 19th century. The work is a detailed examination of the Somerset dialect, featuring a glossary of terms currently used in the area, alongside poems and literary pieces that exemplify the unique linguistic features of the dialect. Jennings seeks to preserve and highlight the regional language, which is characterized by its ancestral ties to the Anglo-Saxon language, making it a significant study for both linguists and enthusiasts of local culture. The opening of the book includes a dedication and prefaces that frame its purpose and significance. Jennings expresses his affection for the West and his desire to document the peculiarities of the Somerset dialect, which he believes retains much of its Anglo-Saxon heritage due to its geographical separation from urban centers. The text features poetic verses that demonstrate local dialectical expressions, and Jennings refers to observations made over years of residence in Somerset, acknowledging contributions made by others in the field of dialect studies. He outlines the dialect's distinct grammatical structures, vocabulary, and sounds, indicating the depth of the work that contributes to the understanding of regional linguistic identity. (This is an automatically generated summary.)
Release date is 2005-02-01
Produced by Miranda van de Heijning, David Starner, and the Online Distributed Proofreading Team
Keywords: English language -- Dialects -- England -- Somerset